Penerapan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Leaflet Dilengkapi LKPD Word Square untuk Meningkatkan Hasil Belajar IPA (Studi Kasus: Siswa Kelas XI di SMA Madrasah Aliyah) - Epa, Kurniyati Wiku; Bano, Vidriana Oktoviana; Enda, Riwa Rambu Hada (Pustaka Digital Indonesia, 2025)
Improving student learning outcomes remains a crucial issue in secondary education, particularly when traditional learning approaches are less effective in fostering active participation and deeper understanding. To address this challenge, this study aimed to describe the implementation of the Student Teams Achievement Division (STAD) type cooperative learning model assisted by leaflet media and equipped with Word Square worksheets (LKPD) in improving student learning outcomes. This research was conducted as classroom action research (CAR) through two cycles, each consisting of planning, implementation, observation, and reflection. The population of the study was class XI students of a private Madrasah Aliyah, with a sample of 20 students selected as research subjects. Data were collected through tests to measure cognitive outcomes, observation sheets to assess affective outcomes, and documentation to support validity. The data were analyzed using descriptive comparative techniques by comparing learning outcomes between cycles I and II. The success indicators were set at ?80% of students achieving the minimum mastery criteria and an increase in the number of students achieving “good” or “very good” affective scores. The results showed that cognitive learning outcomes increased from 80% mastery in cycle I to 95% in cycle II. Affective outcomes also improved, with students obtaining very good and good categories increasing from 10 and 5 in cycle I to 13 and 4 in cycle II, respectively, while the number of students in the “less” category decreased. In conclusion, the implementation of the STAD cooperative learning model assisted by leaflet media and Word Square worksheets effectively improved both cognitive and affective learning outcomes of class XI students.